Object detection using geometric invariant moment - Saad, Puteh; Rizon, Mohamad; Yazid, Haniza; Md. Shakaff, Ali Yeon; Saad, Abdul Rahman; Sugisaka, Masanori; Yaacob, Sazali; Desa, Hazri; Karthigayan, M. (Science Publications, 2006)
Geometric moment invariant produces a set of feature vectors that are invariant under shifting, scaling and rotation. The technique is widely used to extract the global features for pattern recognition due to its discrimination power and robustness. In this paper, moment invariant is used to identify the object from the captured image using the first invariant (Ã˜1). The recognition rate for this technique is 90% after the image undergoes suitable processing and segmentation process